Methamphetamine reduces expressions of tight junction proteins, rearranges F-actin cytoskeleton and increases the blood brain barrier permeability via the RhoA/ROCK-dependent pathway - Xue, Ye; He, Jie-Tao; Zhang, Kai-Kai; Chen, Li-Jian; Wang, Qi; Xie, Xiao-Li (Biochemical and biophysical research communications, 2019)
Methamphetamine (METH) is a psychostimulant with severe neurotoxicity, which is related to an increase of blood-brain barrier (BBB) permeability. However, the exact mechanisms have not been fully illuminated. In the present study, male Sprague Dawley rats were treated with METH or saline with 8 injections (i.p.) at 12-h intervals and sacrificed 24 h after the last METH injection. To evaluate BBB permeability, 6 rats were administered with Evans blue (EB) by tail vein injection 1 h prior to sacrifice. EB levels significantly increased in both left and right frontal lobes in METH-treated rats, suggesting increase of BBB permeability, which was proved by the rearrangement of F-actin cytoskeleton and decreased expressions of tight junction (TJ) proteins in hippocampus. Over-expressions of RhoA, ROCK, myosin light chain (MLC), cofilin, phosphorylation (p)-MLC, p-cofilin and matrix metalloproteinase (MMP)-9 were observed, indicating activated RhoA/ROCK pathway. Rat brain microvascular endothelial cells (RBMECs) were isolated and treated with inhibitors of RhoA and ROCK followed by METH. Pretreatments of the inhibitors significantly decreased expressions of RhoA, ROCK, MLC, cofilin, p-MLC and p-cofilin, increased expressions of TJ proteins, suppressed F-actin cytoskeleton rearrangement and reduced the permeability of RBMECs. These results suggested that METH increased BBB permeability through activating the RhoA/ROCK pathway, which resulted in F-actin cytoskeleton rearrangement and down-regulation of TJ proteins. •METH increased blood brain barrier (BBB) permeability.•METH rearranged F-actin cytoskeleton and decreased tight junction (TJ) proteins.•METH activated RhoA/ROCK pathway.•Inhibition of this pathway decreased F-actin rearrangement and increased TJ proteins.•Inhibition of RhoA/ROCK pathway decreased METH-induced increase of BBB permeability.